Design of lipidic platforms anchored within nanometric cavities by peptide hooks. Issue 52 (12th May 2016) - Messina, G. M. L.; De Zotti, M.; Lettieri, R.; Gatto, E.; Venanzi, M.; Formaggio, F.; Toniolo, C.; Marletta, G.
Abstract : A stable confinement of liposomes within arrays of hybrid polymer/Au nanocavities was achieved using peptide hooks covalently linked to the Au floor. Abstract : Stable confinement of liposomes within arrays of hybrid polymer/Au nanocavities was achieved using peptide hooks covalently linked to the Au floor. The peptide hooks are thiolated analogs of trichogin GA IV (SSTrGA), a well-known broad-spectrum antimicrobial peptide with a high affinity for lipids, functionalized at the N-terminus with an α-lipoic group for linking to Au substrates. SSTrGA promoted opening of the liposomes, giving rise to the formation of a lipid bilayer paving the nanocavity. A patterned nanoporous surface was prepared using a colloidal solution of monodisperse silica nanospheres that formed a cubic close-packed array on the Au substrate. The nanosphere array was then processed using spin coating of a poly(methyl methacrylate) solution, followed by selective removal of the silica nanoparticles, yielding an array of hybrid nanocavities formed with poly(methyl methacrylate) walls and paved with an Au floor. The Au layer was then modified through covalent linkage to SSTrGA, forming a densely packed self-assembled monolayer on the Au floor of the nanowells, as demonstrated using cyclic voltammetry experiments. Atomic force microscopy and a quartz crystal microbalance with dissipation monitoring were used to study the inclusion of the peptide/liposome system in the hybrid nanocavities and the formation of the lipid bilayer inside them. This system could be usefully exploited as a patterned biomimetic environment able to host membrane proteins or lipophilic enzymes for the development of new bioinspired functional materials and for biosensing based on ligand–protein recognition.